Polyamine Putrescine Regulates Oxidative Stress and Autophagy of Hemocytes Induced by Lipopolysaccharides in Pearl Oyster Pinctada fucata martensii - Cao, Yanfei; Jiao, Yu; Zhan, Shuzhi; Liang, Xueru; Li, Zhixin; Chen, Jiayi; Xiong, Xinwei; Gu, Zefeng; Du, Xiaodong; Zheng, Zhe (Frontiers in Physiology, 2021)
The polyamine putrescine (Put) is a ubiquitous small cationic amine. It plays an essential role in controlling the innate immune response. However, little is known about its function in mollusks. In this study, Put content was observed to increase in the serum of pearl oyster Pinctada fucata martensii after 6 and 24 h of lipopolysaccharide (LPS) stimulation. Superoxide dismutase, catalase, and glutathione peroxidase activities increased, and nitric oxide synthase was downregulated in the Put group (combined treatment with Put and LPS) compared with that in the LPS group (combined treatment with PBS and LPS). Furthermore, alkaline phosphatase and acid phosphatase activities were inhibited after 6 h of LPS stimulation. The expression levels of the NF-κB, IKK, JAK, and STAT genes were all significantly suppressed at 12 and 24 h in the Put group. Pseudomonas aeruginosa and Bacillus subtilis grew better after being incubated with the serum from the Put group than that from the LPS group. Additionally, Put treatment remarkably inhibited the autophagy of hemocytes mediated by the AMPK–mTOR–Beclin-1 pathway. This study demonstrated that Put can effectively inhibit the inflammatory response induced by LPS in pearl oysters. These results provide useful information for further exploration of the immunoregulatory functions of polyamines in bivalves and contribute to the development of immunosuppressive agents.